2023
DOI: 10.1097/fjc.0000000000001422
|View full text |Cite
|
Sign up to set email alerts
|

Costunolide Protects Myocardium From Ischemia Reperfusion Injury by Inhibiting Oxidative Stress Through Nrf2/Keap1 Pathway Activation

Abstract: Costunolide (Cos) is a naturally occurring sesquiterpene lactone that exhibits antioxidative properties. In this study, we demonstrate the protective mechanism of Cos against ischemia/reperfusion (I/R)-induced myocardial injury. Cos significantly decreased levels of reactive oxygen species and ameliorated apoptosis of I/R cardiomyocytes both in vitro and in vivo. Further investigation revealed that Cos increased expression of the antioxidant proteins HO-1 and NQO-1 and decreased the Bax/Bcl-2 ratio, thus prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Studies (Kazemirad and Kazerani, 2020;Rodrigo et al, 2022;Li et al, 2023) have shown that oxidative stress is the main factor aggravating MIRI, and the production of a large number of oxygen free radicals can lead to lipid peroxidation of myocardial membrane, which is one of the important mechanisms of reperfusion injury. As an intermediate metabolite of lipid peroxides, MDA can destroy cell membrane structure, lead to changes in cell membrane fluidity and permeability, activation of cell membrane ion channels, myocardial electrophysiological changes, enzyme release in cardiomyocytes, and even failure to maintain normal metabolism of cells, resulting in arrhythmia and myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies (Kazemirad and Kazerani, 2020;Rodrigo et al, 2022;Li et al, 2023) have shown that oxidative stress is the main factor aggravating MIRI, and the production of a large number of oxygen free radicals can lead to lipid peroxidation of myocardial membrane, which is one of the important mechanisms of reperfusion injury. As an intermediate metabolite of lipid peroxides, MDA can destroy cell membrane structure, lead to changes in cell membrane fluidity and permeability, activation of cell membrane ion channels, myocardial electrophysiological changes, enzyme release in cardiomyocytes, and even failure to maintain normal metabolism of cells, resulting in arrhythmia and myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Increased complications and mortality after cardiac perfusion (Braunwald and Kloner, 1985). Reperfusion injury is an extremely complex pathological process, which may lead to a series of pathological reactions including oxidative stress (Li et al, 2023), calcium overload (Li et al, 2021), inflammation (Algoet et al, 2023), autophagy (Xing et al, 2022;Popov et al, 2023) and apoptosis (Zeng et al, 2019). These pathological reactions are exactly the starting points and important mechanisms for research.…”
Section: Introductionmentioning
confidence: 99%